UV SPECTROPHOTOMETRIC ANALYSIS AND VALIDATION OF OSELTAMIVIRPHOSPHATE IN PURE AND PHARMACEUTICAL FORMULATION - YANJANE, SACHIN A.; GHURGHURE, SHRISHAIL M.; MATOLE, VINOD K. (International Journal of Current Pharmaceutical Research, 2020)
Objective: A new, simple, economical, precise, sensitive, linear, accurate, rapid UV spectrophotometric method has been developed for the estimation of Oseltamivir Phosphate in pure form and pharmaceutical formulation. Methods: This UV method was developed using Methanol as a solvent. In the present method, the wavelength selected for analysis was 218 nm. UV-Visible double beam spectrophotometer (Systronic 2201) was used to carry out spectral analysis. The ICH guidelines were used to validate the method. Results: The method was validated for linearity, range, accuracy, precision, robustness, LOD and LOQ. Linearity was found in the range of 10-50µg/ml. Accuracy was performed by using a recovery study. The amount of drug recovered was found to be in the range of 99.01-100.1%. The % RSD value was found to be less than 2. Conclusion: The developed UV spectrophotometric method was found to be simple, economic, sensitive, easy, accurate, linear, specific and highly sensitive and can be used for routine estimation of Oseltamivir Phosphate.